Identification and Characterization bacteria Pseudomonas on Metal Contaminated Soil indicated - Yoyon Suyono; Farid Salahudin (Biopropal Industri, 2011)
The research goals to determine the species of bacteria that can live in soil containing metal as a source of biomaterial biosorben. The research was conducted through the stages of isolation and characterization by testing the morphology, growth and biochemistry. Two isolates which have characteristics similar to the Pseudomonas genus and species of Pseudomonas sp. Pseudomonas sp has the ability to grow in extreme conditions.